Metallo- β-lactamase-Producing Clinical Isolates of Klebsiella pneumoniae from Cancer Patients Visiting Nepal Cancer Hospital, Lalitpur - Chhetri, Archana Katuwal; Dhakal, Hari Prasad; Gurung, Banita; Adhikari, Sanjib; Sharma, Supriya; Raj Banjara, Megha; Raj Rijal, Komal; Ghimire, Prakash (Journal of College of Medical Sciences-Nepal, 2025)
Background The emergence of metallo-beta-lactamase (MBL)-producing bacterial pathogens, particularly Klebsiella pneumoniae, poses a significant challenge in the treatment of infections in immunocompromised populations such as cancer patients. This study aims to investigate the prevalence of MBL-producing Klebsiella pneumoniae, identify associated risk factors for MBL production, and determine their antimicrobial susceptibility pattern among cancer patients in Nepal. Methods A hospital-based, cross-sectional study was conducted on cancer patients from June 2023 to May 2024 in a tertiary care cancer hospital of Nepal. Samples received at the hospital were processed as per standard protocol for isolation, phenotypic identification and antibiotic susceptibility testing following CLSI guideline (2021). Results Out of 3,504 cancer patients, 241 non-duplicate cases of Klebsiella pneumoniae infection were identified. Among these isolates, the majority were obtained from urine samples (101; 42%), followed by sputum samples (61, 25.3%). A total of 104 isolates (43.2%) were confirmed as MBL (metallo-β-lactamase) producers. These MBL-producing isolates exhibited significantly higher resistance to all tested antibiotics compared to non-MBL producers. Statistical analysis revealed that prolonged hospitalization, prior use of broad-spectrum antibiotics, and the presence of fever were significantly associated with MBL production among K. pneumoniae isolates in cancer patients. Conclusion This study demonstrates a high prevalence of MBL-producing Klebsiella pneumoniae among cancer patients in Nepal, with these strains showing significantly elevated resistance to commonly used antibiotics underscoring the need for targeted infection control strategies and strict antimicrobial stewardship in oncology settings.